Views of Police and policing: An examination of public views of patrol method of Crime prevention in Southern Senatorial District of Cross River State, Nigeria - EZIKEUDU, Chukwudi Charles; OPARA, Ikechukwu Jonathan; OKORIE , Chimaobi; EDET, Francis Felix; EJA, Terrence Richard; ONYEMA, Okwu Augustina; AKWAJI, Fidelis Ngaji; NJOKU, Raymond Amanzie; ABUNIMYE, Sunday Betembiaye; BASSEY, Ugo Samuel; ODINKA, Godfrey Ekene; ISOKON, Brown (Journal of Ecohumanism, 2024)
Precisely, this study examined public view of police patrol as a technique of policing for crime prevention. Cross-sectional survey study design, requiring the use of qualitative and quantitative methods was adopted. Data was collected from 840 answerers from purposively selected local government area of the Southern Senatorial Locality of Cross River State consisting 420 males and 420 females chosen from multistage probability in addition to non-probability sampling techniques. The instrument of data collection was questionnaire which incorporated open and closed-ended questions in addition to structured and unstructured oral interview. Data were analysed by means of descriptive and inferential statistical tools. Particularly, a simple percentage method of data analysis was engaged for the analysis of the research question while chi-square statistical tool was utilized to test the research hypothesis. To lead the research, one research hypothesis was raised and tested using correlation statistical tool. The research discovered that there is a strong significant relationship between public positive views of police patrol technique of policing for crime prevention and police activity. The analysis showed the correlation coefficient of 0.492 indicating the existence of relationships between public positive views of police patrol technique of crime prevention are likely to enhance policing and police activity. The test was significant at 0.01 levels (1-tailed) and led to the rejection of the null hypothesis which finds no significant relationship. Following the research findings, the subsequent policy recommendations were made among which include: police commissioner should enhance patrolling especially in crimogenic zone thereby preventing crime and anti-social behavior from occurring, while still engage in reactive patrol, police should as well engage the neighbourhood watch.